Crab herbivory regulates plant facilitative and competitive processes in argentinean marshes - Alberti, Juan (2008)
Interactions among plants have been hypothesized to be context dependent, shifting between facilitative and competitive in response to variation in physical and biological stresses. This hypothesis has been supported by studies of the importance of positive and negative interactions along abiotic stress gradients (e.g., salinity, desiccation), but few studies have tested how variation in biotic stresses can mediate the nature and strength of plant interactions. We examined the hypothesis that herbivory regulates the strength of competitive and facilitative interactions during succession in Argentinean marshes dominated by Spartina densiflora and Sarcocornia perennis. Spartina densiflora is preferred by the dominant herbivore in the system, the crab Chasmagnathus granulatus. We experimentally manipulated crab herbivory, plant structure, and shade, and we found that, when herbivory was low in the spring and summer, competitive interactions between plants were dominant, but in the fall, when herbivory was highest, facilitative interactions dominated, and Spartina densiflora survival was completely dependent upon association with Sarcocornia perennis. Moreover, experimental removal of Sarcocornia perennis across recently disturbed tidal flats revealed that, while Sarcocornia perennis positively affected small Spartina densiflora patches by decreasing herbivory, as patch size increases and they can withstand the impact of herbivory, competitive interactions predominated and Spartina densiflora ultimately outcompeted Sarcocornia perennis. These results show that herbivory can mediate the balance between facilitative and competitive processes in vascular plant communities and that the strength of consumer regulation of interactions can vary seasonally and with patch size